A reactive oxygen species-replenishing coordination polymer nanomedicine disrupts redox homeostasis and induces concurrent apoptosis-ferroptosis for combinational cancer therapy. (1st October 2022) - Zhang, Zhuangzhuang; Pan, Yang; Cun, Ju-E; Li, Junhua; Guo, Zhaoyuan; Pan, Qingqing; Gao, Wenxia; Pu, Yuji; Luo, Kui; He, Bin
Abstract: Reactive oxygen species (ROS) are important signal molecules and imbalanced ROS level could lead to cell death. Elevated ROS levels in tumor tissues offer an opportunity to design ROS-responsive drug delivery systems (DDSs) or ROS-based cancer therapies such as chemodynamic therapy. However, their anticancer efficacies are hampered by the ROS-consuming nature of these DDSs as well as the high concentration of reductive agents like glutathione (GSH). Here we developed a doxorubicin (DOX)-incorporated iron coordination polymer nanoparticle (PCFD) for efficient chemo-chemodynamic cancer therapy by using a cinnamaldehyde (CA)-based ROS-replenishing organic ligand (TCA). TCA can ROS-responsively release CA to supplement intracellular ROS and deplete GSH by a thiol-Michael addition reaction, which together with DOX-triggered ROS upregulation and Fe 3+ -enabled GSH depletion facilitated efficient DOX release and enhanced Fenton reaction, thereby inducing redox dyshomeostasis and cancer cell death in a concurrent apoptosis-ferroptosis way. Both in vitro and in vivo studies revealed that ROS-replenishing PCFD exhibited much better anticancer effect than ROS-consuming control nanoparticle PAFD. The ingenious ROS-replenishing strategy could be expanded to construct versatile ROS-responsive DDSs and ROS-based nanomedicines with potentiated anticancer activity. Statement of significance: We develop a doxorubicin (DOX)-incorporated iron coordination polymer nanoparticle (PCFD) for efficient chemo-chemodynamic cancer therapy by using a cinnamaldehyde-based reactive oxygen species (ROS)-replenishing organic ligand. This functional ligand can ROS-responsively release cinnamaldehyde to supplement intracellular H2 O2 and deplete glutathione (GSH) by a thiol-Michael addition reaction, which together with DOX-triggered ROS upregulation and Fe 3+ -enabled GSH depletion facilitates efficient DOX release and enhanced Fenton reaction, thereby inducing redox dyshomeostasis and cancer cell death in a concurrent apoptosis-ferroptosis way. Both in vitro and in vivo studies reveal that ROS-replenishing PCFD exhibit much better anticancer effect than ROS consuming counterpart. This study provides a facile and straightforward strategy to design ROS amplifying nanoplatforms for cancer treatment. Graphical abstract: Image, graphical abstract